Freezing stress response of wild and cultivated chickpeas - Kalve, Shweta; House, Megan Alexandra; Tar’an, Bunyamin (Frontiers in Plant Science, 2024)
Chickpea is an important grain legume globally; however, cold stress has adverse effects on its growth. In cold countries, like Canada where the growing season is short, having cold stress-tolerant varieties is crucial. Some accessions of Cicer reticulatum, a wild relative of chickpeas, can survive under suboptimal environments. In this study, we explored the performance of eleven C. reticulatum accessions and two chickpea cultivars, CDC Leader and CDC Consul, together with a cold sensitive check ILC533 under freezing stress. Freezing tolerance was scored based on a 1-9 scale. The wild relatives, particularly Kesen_075 and CudiA_152, had higher frost tolerance compared to the cultivars, which all died after frost treatment. We completed mRNA sequencing to assess changes in gene expression in response to freezing stress and identified 6,184 differentially expressed genes (DEGs) in CDC Consul, and 7,842 DEGs in Kesen_075. GO (gene ontology) analysis of the DEGs revealed that those related to stress responses, endogenous and external stimuli responses, secondary metabolite processes, and photosynthesis were significantly over-represented in CDC Consul, while genes related to endogenous stimulus responses and photosynthesis were significantly over-represented in Kesen_075. These results are consistent with Kesen_075 being more tolerant to freezing stress than CDC Consul. Moreover, our data revealed that the expression of CBF pathway-related genes was impacted during freezing conditions in Kesen_075, and expression of these genes is believed to alleviate the damage caused by freezing stress. We identified genomic regions associated with tolerance to freezing stress in an F2 population derived from a cross between CDC Consul and Kesen_075 using QTL-seq analysis. Eight QTLs (P<0.05) on chromosomes Ca3, Ca4, Ca6, Ca7, Ca8, and two QTLs (P<0.01) on chromosomes Ca4 and Ca8, were associated with tolerance to freezing stress. Interestingly, 58 DEGs co-located within these QTLs. To our knowledge, this is the first study to explore the transcriptome and QTLs associated with freezing tolerance in wild relatives of chickpea under controlled conditions. Altogether, these findings provide comprehensive information that aids in understanding the molecular mechanism of chickpea adaptation to freezing stress and provides potential candidate genes that can assist in breeding of freezing tolerant varieties.